CRISPR/Cas9 Genome Editing Technology: A Valuable Tool for Understanding Plant Cell Wall Biosynthesis and Function - Zhang, Yuan; Showalter, Allan M. (Frontiers in Plant Science, 2020)
For the past five years, Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/Cas9) technology has appeared in the molecular biology research spotlight. As a game-changing player in genome editing, CRISPR/Cas9 technology has revolutionized animal research, including medical research and human gene therapy as well as plant science research, particularly for crop improvement. One of the most common applications of CRISPR/Cas9 is to generate genetic knockout mutants. Recently, several multiplex genome editing approaches utilizing CRISPR/Cas9 were developed and applied in various aspects of plant research. Here we summarize these approaches as they relate to plants, particularly with respect to understanding the biosynthesis and function of the plant cell wall. Plant cell wall is a polysaccharide-rich cell structure that is vital to plant cell formation, growth, and development. Humans are heavily dependent on the byproduct of the plant cell wall such as shelter, food, clothes, and fuel. Genes involved in the assembly of the plant cell wall are often highly redundant. To identify these redundant genes, higher-order knockout mutants need to be generated, which is conventionally done by genetic crossing. Compared with genetic crossing, CRISPR/Cas9 multi-gene targeting can greatly shorten the process of higher-order mutant generation and screening, which is especially useful to characterize cell wall related genes in plant species that require longer growth time. Moreover, CRISPR/Cas9 makes it possible to knock out genes when null T-DNA mutants are not available or are genetically linked. Because of these advantages, CRISPR/Cas9 is becoming an ideal and indispensable tool to perform functional studies in plant cell wall research. In this review, we provide perspectives on how to design CRISPR/Cas9 to achieve efficient gene editing and multi-gene targeting in plants. We also discuss the recent development of the virus-based CRISPR/Cas9 system and the application of CRISPR/Cas9 to knock in genes. Lastly, we summarized current progress on using CRISPR/Cas9 for the characterization of plant cell wall-related genes.